Combination design and performance evaluation of conductive bonding layer for asphalt pavement active deicing. (10th December 2020) - Wang, Chaohui; Fu, Hao; Ma, Wanbin; Zhang, Zhifang; Ji, Xiaoping; Han, Xiaoxia
Highlights: The pavement conductive interlayer bonding materials were prepared. The temperature rise effect of the conductive bonding layer in pavement structure was evaluated. The feasibility of using conductive bonding layer to realize the pavement deicing and snow melting was verified. Abstract: The purpose is to realize the environmental friendliness and sustainability of pavement active deicing and snow melting. Different types of SBS modified asphalt conductive bonding materials for pavement interlayer bonding and melting ice and snow were prepared. The effects of conductive phase materials, electrodes and spacing on the conductivity and heat generation of conductive bonding layer were studied. The heating effect of SBS modified asphalt conductive bonding layer in pavement structure was analyzed. The feasibility of converting electric energy into heat energy by conductive bonding layer to realize melting ice and snow on pavement was verified. It provides a new direction for the research and application of green active deicing and snow melting. The results show that the carbon fiber conductive bonding layer had the best conductivity. At the constant temperature of −5 °C, the surface temperature of the pavement structure could reach above 0 °C after the conductive bonding layer was electrified for 100 min under 36 V voltage, which can realize the deicing and snow melting of the pavement. The distribution of carbon fiber has a certain adverse effect on the bonding performance of conductive bonding layers, but it still shows good bonding performance, water resistance and temperature change resistance.